Placental and Fetal Disposition of Mercuric Ions in Rats Exposed to Methylmercury: Role of Mrp2 - Bridges, Christy C. (2012)
Methylmercury is a prevalent environmental toxicant that can have deleterious effects on a developing fetus. Previous studies indicate that the multidrug resistance-associated protein 2 (Mrp2) is involved in renal and hepatic export of mercuric ions. Therefore, we hypothesize that Mrp2 is also involved in export of mercuric ions from placental trophoblasts and fetal tissues. To test this hypothesis, we assessed the disposition of mercuric ions in pregnant Wistar and TR(–) (Mrp2-deficient) rats exposed to a single dose of methylmercury. The amount of mercury in renal tissues (cortex and outer stripe of outer medulla), liver, blood, amniotic fluid, uterus, placentas and fetuses was significantly greater in TR(–) rats than in Wistar rats. Urinary and fecal elimination of mercury was greater in Wistar dams than in TR(–) dams. Thus, our findings suggest that Mrp2 may be involved in the export of mercuric ions from maternal and fetal organs following exposure to methylmercury.